CONTRADICTIONS AND PROSPECTS OF EARLY SPORTS SPECIALIZATION IN CHILDREN'S AND YOUTH SPORTS (Physical Culture and Sport: Scientific Perspective, 2025)
The development of modern sports increasingly necessitates the search for effective ways to train athletes from an early age. The intensification of international competition and the emphasis on achieving high sports results during youth years have led to the active implementation of early specialization in children's and youth sports. This approach involves a targeted focus on one sport, with minimal reliance on general physical training methods and other types of physical activity. At first glance, this strategy creates opportunities for faster acquisition of technical and tactical skills, enhanced sports performance, and the establishment of prerequisites for a future sports career. However, numerous scientific studies and practical observations highlight several contradictions associated with early specialization. Key issues include an increased risk of overstrain and injuries to the musculoskeletal system, limitations in the development of coordination abilities, disruptions in proportional physical development, reduced motivation and interest in sports due to psychological burnout. Particularly concerning is that early specialization is often accompanied by a lack of comprehensive physical and emotional development, which can negatively impact the child's personality formation and their future in sports.Thus, a fundamental contradiction arises: between the necessity for achieving quick results in children's and youth sports and the need to preserve health, ensure harmonious development, build long-term work capacity, and sustain motivation for sports activities.Analysis of contemporary research indicates that the professional training of a coach-instructor in youth sports should integrate pedagogical, psychological, medical-biological, and innovative components within a clear structure encompassing theoretical, methodological, practical, and reflexive elements. The role of the family and social environment in shaping the sports milieu, alongside the psychological and physiological characteristics of adolescents that determine their developmental specificity, are examined. Synthesizing international and domestic studies highlights the lack of convincing evidence supporting the benefits of early sports specialization for most sports types and the significant risks, including increased injury rates and psychosocial issues. Simultaneously, emphasis is placed on preventing overload, burnout, and ensuring the harmonious development of children and adolescents. Future scientific endeavors should prioritize longitudinal comparisons of athlete training models, optimization of selection systems, and enhancement of educational programs for coaches.The conducted study revealed that the phenomenon of early sports specialization in youth sports has a contradictory nature. On the one hand, it ensures the rapid development of specialized skills and provides certain advantages in sports disciplines with an early performance peak. On the other hand, numerous scientific findings and practical observations confirm the presence of serious risks associated with overexertion, injuries, disproportionate physical development, psychological exhaustion, and reduced motivation. The systematization of current research indicates a lack of compelling evidence supporting the long-term benefits of early sports specialization for most sports and highlights the predominance of its negative consequences over potential advantages. Therefore, the advisability of early sports specialization requires critical reevaluation, and the training of young athletes should be based on principles of versatility, individualization, health preservation, and long-term perspective. A key factor is the professional preparation of the coach-teacher, which encompasses pedagogical, psychological, medical-biological, and innovative components, as well as close interaction with parents and the social environment.
Keywords: youth sports; early sports specialization; research